رواية "سيدات زحل" للروائية لطفية الدليمي دراسة سوسيو- تاريخية - أسود, نوزاد أحمد (Sulaimani Journal for Humanities, 2025)
The novel recounts the tragic events of Iraq in two different eras in the history of the country: the Ottoman era, and the fall of Baghdad in 2003. The story is narrated by the female protagonist, Hayat Al-Babily (The Babylonian), whois an intellectual, liberal journalist. Following the fall of Baghdad, we learn that Hayat is not usedto the new atmosphere and, along with her family, relatives and female friends, isshocked and torn apart by crimes of killing, decapitation, rape and kidnap, committed by masked and beardedfightersofvarious armed groups and religious hardliners. The book is in 9 chapters, which are divided into 35 scenes, each scene with a subtitle. Chapter 1 contains three introductory titles with three scenes. Some of the events are narrated by the main character Hayat, and some by other women. All the events are about love, death, loss, rape, kidnap, dismemberment, beheading and amputation of the limbs and tongue, in addition to stories of tolerance and coexistence of different religions, communities and cultures in differentperiods of Iraqi history. This novel is considered as a literary testimony of the suffering of the Iraqi people in two identicalperiods of time.